Efektivitas Home Based Exercise Training (HBET) terhadap kualitas hidup pasien gagal jantung - Rendi Kurniawan; Djunizar Djamaludin; Usastiawaty Cik Ayu Saadiah Isnainy (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: In Indonesia, physical training is carried out centrally in hospitals. Official data on the coverage and participation of this program in heart failure patients in Indonesia have not been obtained. Home-based exercise training (HBET) can be an option for physical exercise and an alternative solution in order to reduce patients' participation in physical exercise. HBET is a programmed physical exercise that patients can perform independently at home.Purpose: To examine the effects of home-based exercise training (HBET) on the quality of life in patients with heart failure.Method: One group pretest-posttest design was employed with purposive sampling technique. The sample used was 15 participants who were outpatients at Gedong Air Community Health Center, Bandar Lampung City. Participants were given the Home-based exercise training (HBET) program for 14 days subsequently the participants was measured using the Minesota Living with Heart Failure Quistionaire to determine the quality of life.Results: There is an effect of home based exercise training (HBET) on the quality of life of patients with heart failure with p-value of 0.000. The mean score of quality of life before being given home based exercise training (HBET) is 35.93 ± 6.770 and the mean score after giving intervention is 57.13 ±7,469.Conclusion: There is an effect of home-based exercise training (HBET) on the quality of life of patients with heart failure.Suggestion: This physical exercise home-based exercise training (HBET) should be an integral part of the rehabilitation program for patients with heart failure after discharge from the hospital so that it can reduce rehospitalizations and improve quality of life.Keywords: Home Based Exercise Training (HBET); Quality of Life; Patients; Heart Failure.Pendahuluan: Di Indonesia latihan fisik dilakukan secara terpusat di rumah sakit. Data resmi tentang cakupan dan partisipasi program ini pada pasien gagal jantung di Indonesia belum didapatkan. Home-based exercise training (HBET) dapat menjadi salah satu pilihan latihan fisik dan alternative solusi rendahnya partisipasi pasien mengikuti latihan fisik. HBET merupakan latihan fisik terprogram yang dapat dijalankan oleh pasien secara mandiri di rumah.Tujuan: Untuk menilai pengaruh home-based exercise training (HBET) terhadap kualitas hidup pasien gagal jantung.Metode: Rancangan penelitian one group pretes-postes design dengan tehnik sampling yaitu purposive samping. Sampel yang digunakan sebanyak 15 partisipan yang merupakan pasien rawat jalan di Puskesmas Gedong Air Kota Bandar Lampung. Pada saat intervensi partisipan diberikan program Home-based exercise training (HBET) selama 14 hari kemudian setelah itu di ukur menggunakan Minesota Living with Heart Failure Quistionaire untuk mengetahui kualitas hidupnya.Hasil: Terdapat pengaruh home based exercise training (HBET) terhadap kualitas hidup pasien gagal jantung dengan nilai p-value 0,000. Nilai rata-rata kualitas hidup sebelum diberikan home based exercise training (HBET) yaitu 35,93 dengan standar deviasi 6,770 dan nilai rata-rata sesudahnya yaitu 57,13 dengan standar deviasi 7,469.Simpulan: Ada pengaruh home based exercise training (HBET) terhadap kualitas hidup pasien gagal jantung.Saran: Latihan fisik home based exercise training (HBET) ini hendaknya menjadi bagian integral program rehabilitasi pasien gagal jantung setelah pulang dari rumah sakit sehingga dapat menurunkan rawat inap dan meningkatkan kualitas hidup.